Trusting God’s Redemption On Psalm 130: A Literary-Structure Approached - Philip Suciadi Chia; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
The pressures of life that cause suffering are real things in life. The same thing happened to the psalmist recorded in Psalm 130:1-8. There are two big possibilities when someone faces a problem, they will move away from God or draw closer to God. In the narrative of Psalm 130:1-8, the psalmist draws closer to God. When the psalmist trusting God’s redemption generates the attitude to wait upon the Lord. Although God has not heard my prayer yet, I want to trust the Lord that he will deliver me despite I do not know when he will release me. I want to live in trust to the Lord because I believe that my faith will help me to endure in my problems, to still wait upon the Lord. I want to remember his characters so that I do not want to lose my faith in the midst of my suffering. This Psalm is begun with petition to the Lord and it is ended up by describing God’s characteristic.